O022 For each HLA-DRB1 genotype, the likelihood to develop RA correlates with the probability of binding at least a peptide from PAD4. (21st February 2018) - Balandraud, N; Auger, I; Texier, G; Roudier, J
Abstract : Introduction: The production of IgG ACPA can be helped by T lymphocytes specific for PADs, the enzymes that transform arginin into citrullin. Thus, the molecular basis for the HLA-DRB1 association with RA might be the capability for the two alleles encoded by a given HLA-DRB1 genotype to bind PAD4 derived peptides. 1 We recently published a table showing that the relative risk to develop ACPA positive RA for the 106 most common genotypes. 2 French HLA-DRB1 genotypes varies from 28 to 0.2. For a given HLA-DRB1 genotype, the risk to develop RA should be correlated with the probability for the two HLA-DRB1 molecules encoded by this genotype to bind peptides from PAD peptides. Objectives: To test whether the risk of developing ACPA positive RA for each HLA-DRB1 genotypes correlates with the probability for the 2 HLA-DR alleles encoded by each genotype to bind at least one PAD4 peptide. Methods: 65 Synthetic peptides (20 mers) of human PAD4 and 167 peptides encompassing the A and B chains of human fibrinogen were synthesised in solid phase. Whenever there was an arginine residue, both the arginine and the citrullin variant were synthesised. In the end, we had 25 fibrinogen peptides containing neither arginin nor citrulline, 71 citrullinated and 71 arginine peptides from fibrinogen . HLA-DRB1 peptide binding studies were performed by adding one microgram of purified HLA-DRB1 to ELISA wells coated with 10 micrograms PAD peptide. Bound HLA-DR was revealed by biotinylated anti HLA-DR antibody followed by peroxidase conjugated avidin. Statistical analyses: Correlation between HLA-DRB1 genotypic risk for RA and Likelihood to bind PAD4 for a given genotype was evaluated by Spearman's Results: HLA-DRB1 genotypic risks to develop RA correlate with likelyhood to bind PAD4 peptides (p=0.06, Pearson's), not citrullinated Fibrinogen peptides (p>0.6 and p>0.9). Conclusions: HLA-DRB1 genotypes are associated with a risk to develop RA and a likelihood to bind at least one of 65 overlapping PAD4 peptides. The strong correlation between these two parameters suggest that PAD4 peptide binding to HLA-DRB1 may be the basis of the HLA-DRB1 RA association. Such correlation is not observed when testing the binding of citrullinated or native peptides from Fibrinogen to HLA-DRB1 molecules. References: . Fanny Arnoux, Charlotte Mariot*, Elisa Peen*, Nathalie Lambert, Nathalie Balandraud, Jean Roudier, Isabelle Auger. Peptidyl arginine deiminase immunisation induces anti-citrullinated protein antibodies in mice with particular MHC types. PNAS 2017. . Nathalie Balandraud, Christophe Picard, Denis Reviron, Cyril Landais, Eric Toussirot, Nathalie Lambert, Emmanuel Telle, Caroline Charpin, Daniel Wendling, Etienne Pardoux, Isabelle Auger, Jean Roudier. HLA DR and the risk of developping RA. Plos One2013. Disclosure of interest: None declared